Method to reinforce polylactic acid with cellulose nanofibers via a polyhydroxybutyrate carrier system. (20th April 2016) - Kiziltas, Alper; Nazari, Behzad; Erbas Kiziltas, Esra; Gardner, Douglas J.; Han, Yousoo; Rushing, Todd S.
Highlights: PLA/PHB/cellulose nanocomposites were prepared by a melt compounding technique. Elastic modulus at low frequencies increased with increasing CNF content. CNF composites exhibited strong shear thinning behavior. Carrier systems, PHB, lead to better dispersion of CNF in the PLA matrix. No pre-drying of the CNF was required before the compounding. Abstract: The elastic moduli of PLA reinforced with 5 and 10 wt.% CNF with the carrier, at a frequency ( ω ) of 0.07, were 67% and 415% higher, respectively, than that of neat PLA. The shear viscosity at a shear rate of 0.01 ( η 0.01 ) for PLA + 10 wt.% CNF was 32% higher than that of the neat PLA matrix. The η 0.01 of PLA reinforced with 5 wt.% CNF and the PHB carrier was similar to neat PLA. The tensile and flexural moduli of elasticity of the nanocomposites continuously increased with increased CNF loading. The results of the mechanical property measurements are in accordance with the rheological data. The CNF appeared to be better dispersed (less-aggregated nanofibers) in the PLA reinforced with 5 wt.% CNF and the PHB carrier. Possible applications for the composites studied in this research are packaging materials, construction materials, and auto parts for interior applications.